A case report of congenital lobar emphysema - K., Aditya; K., Parvathi; V., Prabhakar (International Journal of Contemporary Pediatrics, 2020)
Congenital lobar emphysema (CLE), also known as congenital alveolar overdistension, is a developmental anomaly of the lower respiratory tract that is characterized by hyperinflation of one or more of the pulmonary lobes. CLE is a rare congenital malformation with a prevalence of 1 in 20,000 to 1 in 30,000. We are reporting a 4-month-old boy presented with complaints of cough and cold for 3 days with history of similar complaints in the past at age of 1month and 2 months. Investigations revealed hyperlucency of left upper zone with tracheal shift and mild shift of the heart to the right. Elective Left Upper Lung Lobectomy was done and Appropriate supportive therapy given and child recovered well.